Nationwide 5GHz-fixed wireless network for prototype rain alarm system - Guico, Maria Leonora (Archīum Ateneo, 2015)
We present the first results of a nationwide experiment that uses 5GHz fixed wireless network as a rain alarm system through monitoring the changes in received signal levels. This paper proposes an alternative framework and correlation approach for rain sensing, which rely mainly on the attenuation from broadband wireless systems. Unique to this system is an automatic reporting of received signal levels coming from a central location that gathers data of one-minute resolution from SmartBro subscribers. The SmartBro wireless system is one of the largest deployments in the world composed of 5 GHz links, which may help in reinforcing rain data collection due to their ubiquity of deployment in the Philippines, with nearly 20,000 land-based antennas. To demonstrate this capability, we selected eastern seaboard cities near the Pacific Ocean with fixed wireless subscribers virtually at random, and studied the changes from baseline attenuation during strong rain events. The reckoning method comprises of (1) baselining method to determine signal loss in normal weather condition, (2) sigma scheme technique that uses the variation of the signal in order to determine rain presence. Lastly, we also made a visualization tool for highly intense precipitation events. Time series videos of signal loss in the Philippines, with plotted location-specific signal loss data were developed for key meteorological events in the past two years: of which include the Southwest Monsoon season in 2012 and the devastation of Typhoon Haiyan in 2013.